Whistle-Blowers: How Much We Can Learn From Them Depends on How Much We Can Give Up - Alford, C. Fred (American behavioral scientist, 1999)
Based on intensive interviews with several dozen whistle-blowers, this article asks what they have to teach about the organizations in which they worked. The most important thing they have to teach is that organizations are deeply threatened by what Kant called ethical autonomy (Mündigkeit). Organizational life is dedicated to the destruction of ethical autonomy for much the same reason that Freud saw social life as dedicated to the suppression of sex and aggression. Ethical autonomy threatens to explode the organization. This may not in fact be the case, but most organizations act as if they believe it. The purpose of sacrificing the whistle-blower is to prevent the outbreak of an epidemic of ethical and moral responsibility that threatens to engulf the organization in a competitive world.